Boron isotope variability related to boron speciation (change during uptake and transport) in bell pepper plants and SI traceable n(11B)/n(10B) ratios for plant reference materials. (13th June 2019) - Geilert, Sonja; Vogl, Jochen; Rosner, Martin; Eichert, Thomas
Abstract : Rationale: Boron (B) is an essential micronutrient in plants and its isotope variations are used to gain insights into plant metabolism, which is important for crop plant cultivation. B isotope variations were used to trace intra‐plant fractionation mechanisms in response to the B concentration in the irrigation water spanning the range from B depletion to toxic levels. Methods: A fully validated analytical procedure based on multi‐collector inductively coupled plasma mass spectrometry (MC‐ICP‐MS), sample decomposition and B matrix separation was applied to study B isotope fractionation. The validation was accomplished by establishing a complete uncertainty budget and by applying reference materials, yielding expanded measurement uncertainties of 0.8‰ for pure boric acid solutions and ≤1.5‰ for processed samples. With this validated procedure SI traceable B isotope amount ratios were determined in plant reference materials for the first time. Results: The B isotope compositions of irrigation water and bell pepper samples suggest passive diffusion of the heavy 11 B isotope into the roots during low to high B concentrations while uptake of the light 10 B isotope was promoted during B depletion, probably by active processes. A systematic enrichment of the heavy 11 B isotope in higher located plant parts was observed (average Δ 11 Bleaf‐roots = 20.3 ± 2.8‰ (1 SD)), possibly by a facilitated transport of the heavy 11 B isotope to growing meristems by B transporters. Conclusions: The B isotopes can be used to identify plant metabolism in response to the B concentration in the irrigation water and during intra‐plant B transfer. The large B isotope fractionation within the plants demonstrates the importance of biological B cycling for the global B cycle.